Original methods and tools of the investigations of the body balance disturbation tolerance skills of the Polish judo athletes from 1976 to 2016 - Maslinski, J.; Piepiora, P.; Cieslinski, W.; Witkowski, K. (Archives of Budo, 2017)
Background and Study Aim: In judo and other combat sports the specificity of maintaining a stable posture is related to the distortions generated by the competitor and own offensive activity as well as defensive or motoric preparatory actions. An effect of the body balance disturbation tolerance skills (BBDTS) is situations when athlete maintains contact with the ground with only one leg and often only part of the foot in conditions of great dynamics of action of both sides. Meanwhile recommended balance tests (especially so-called static balance) based on maintaining the stable posture for the relatively long time. It does not matter if person is standing on one leg (e.g. Flamingo Balance Test). Lack of the most important factor - disturbance of balance by external forces and/or their own dynamic activity. The purpose of this review is to knowledge about the original evaluate methods and results of the BBDTS by the Polish judo athletes from 1980 to 2016.